Health problems and lifestyles of uninsured immigrants: a report from a free health check-up at a hospital in Japan - Haruka Ando; Yoshitaka Nishino; Noriko Aizawa; Kyo Takahashi; Akiyo Itagaki (BMC Research Notes)
Abstract Objective Immigrants living in unstable conditions face challenges in improving their health. Research on the associations between health problems and lifestyle factors remains limited. We aimed to gather information on the health issues and lifestyles of immigrants experiencing financial instability while residing in Japan. Results A mixed-method approach was employed to collect data from participants attending a free health check-up organised by non-profit Organisation A and Hospital B in the Northern Kanto region. Among 41 participants, with unstable employment status, 18 young Asian adults consented to provide their health check-up results and participated in a questionnaire-based survey regarding their health and lifestyle changes before and after arriving in Japan. The changes of sleeping duration, exercise time, alcohol consumption, smoking habits, and emotional state were analysed, and only sleeping duration was significantly decreased. The findings indicated a need for medical treatment, detailed examinations, and oral care, due to increased risks of non-communicable diseases and missing teeth. The respondents reported reduced sleep while some deteriorated physical exercise and emotional states at the present time. Three participants who consented to interviews discussed their lifestyle-related issues. Improved social policies and healthcare access, and social support for immigrants with unstable employment are needed.